An analysis of the musical interpretations of Nina Simone - Freyermuth, Jessie L. (Kansas State University, 2010)
Nina Simone was a prominent jazz musician of the late 1950s and 60s. Beyond her fame as a jazz musician, Nina Simone reached even greater status as a civil rights activist. Her music spoke to the hearts of hundreds of thousands in the black community who were struggling to rise above their status as a second-class citizen. Simone’s powerful anthems were a reminder that change was going to come. Nina Simone’s musical interpretation and approach was very unique because of her background as a classical pianist. Nina’s untrained vocal chops were a perfect blend of rough growl and smooth straight-tone, which provided an unquestionable feeling of heartache to the songs in her repertoire. Simone also had a knack for word painting, and the emotional climax in her songs is absolutely stunning. Nina Simone did not have a typical jazz style. Critics often described her as a “jazz-and-something-else-singer.” She moved effortlessly through genres, including gospel, blues, jazz, folk, classical, and even European classical. Probably her biggest mark, however, was on the genre of protest songs. Simone was one of the most outspoken and influential musicians throughout the civil rights movement. Her music spoke to the hundreds of thousands of African American men and women fighting for their rights during the 1960s. Although Simone is remembered for the lyrics she sang and the emotions she evoked, not enough credit is given to her as an interpreter of song. Simone had an incredible talent at finding the true message of a song and exposing it to her audience. Rather than jazz musician or activist, this thesis will focus on Simone as a gifted interpreter.
Keywords: Nina Simone, musical interpretations, activist; Music (0413)